Komunitas Moluska pada Berbagai Kondisi Mangrove di Segara Anakan, Cilacap-Jawa Tengah - Nova Mujiono; Nur Rohmatin Isnaningsih (Jurnal Kelautan Tropis, 2022)
The mangrove forest in Segara Anakan lagoon continues to decrease from land conversion or sedimentation. It could have an impact on the diversity of molluscs. This study aims to inventory the diversity and the patterns of mangrove molluscs communities in the Segara Anakan lagoon area. The method used was a 5x5 m2 sample plot in five different mangrove forest cover conditions (dense mangroves, sparse mangroves, planted mangroves, Nipah, and open land). Each category is represented by two stations. The research was inventorying 19 species of molluscs from eight families. The species with the highest number of individuals was Cerithidea weyersi (26.53% of the population). The species with the widest distribution were Littoraria carinifera and Neripteron violaceum. In general, the molluscs communities found from the Segara Anakan Lagoon have moderate diversity, low dominance, and high evenness. The number of individuals and species based on the category of mangrove habitat conditions varies greatly. In dense mangroves (M1) found 119 individuals from 12 species, sparse mangroves (M2) 278 individuals from 15 species, planted mangroves (MT) 129 individuals from 7 species, Nipah (N) 36 individuals from 6 species, and in open land ( LT) collected 29 individuals from 7 species. The data show that sparse mangroves are preferred by molluscs when compared to dense mangroves. Our studies also added 6 species as new records from the Segara Anakan location, thereby increasing the number of molluscs diversity in the area become 61 species.